Fungsi Pengawasan dan Motivasi Kerja terhadap Kinerja Pegawai: Peran Tingkat Pendidikan Sebagai Pemoderasi - Muhammad Basyir; Sulaiman (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2022)
This study analyzes the effect of supervision and works motivation on civil servants' performance by assigning the education levels as a moderator in the functional relationship. The samples are 250 civil servants working in the local government agency of Banda Aceh city. Furthermore, the statistical model used consists of multiple regression and moderated regression analysis. The study discovered that civil servants' performance is positively affected by supervision and work motivation. The education level not only affects performance positively and significantly but also moderates the work motivation-performance relationship. However, education level does not moderate the effect of supervision on civil servants' performance.